2017
DOI: 10.3389/fimmu.2017.00598
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Gut As a Danger Signal for Autoimmune Diseases

Abstract: The intestinal epithelial lining, together with factors secreted from it, forms a barrier that separates the host from the environment. In pathologic conditions, the permeability of the epithelial lining may be compromised allowing the passage of toxins, antigens, and bacteria in the lumen to enter the blood stream creating a “leaky gut.” In individuals with a genetic predisposition, a leaky gut may allow environmental factors to enter the body and trigger the initiation and development of autoimmune disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
349
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(370 citation statements)
references
References 145 publications
(162 reference statements)
6
349
0
15
Order By: Relevance
“…. We also measured the bacteria-specific IgA levels in the serum as an index of gut permeability due to loss of gut tolerance (48)(49)(50). While there was a systemic decrease in total IgA ( Figure 3I), we observed that B cell-specific GARP-KO mice had a significant increase in IgA level against gut bacteria ( Figure 3J).…”
Section: Independent Experiments) (H) Cd19mentioning
confidence: 93%
“…. We also measured the bacteria-specific IgA levels in the serum as an index of gut permeability due to loss of gut tolerance (48)(49)(50). While there was a systemic decrease in total IgA ( Figure 3I), we observed that B cell-specific GARP-KO mice had a significant increase in IgA level against gut bacteria ( Figure 3J).…”
Section: Independent Experiments) (H) Cd19mentioning
confidence: 93%
“…The gut barrier comprises a physical barrier, a biochemical barrier and an immune system barrier 28. The physical barrier is supported mainly by the mucus layer, microbes and a single layer of intestinal epithelial cells that are linked by tight junction proteins.…”
Section: Gut Barrier Dysfunction In Patients With Nafldmentioning
confidence: 99%
“…Molecules with antimicrobial properties, such as bile acids and antimicrobial proteins (including α-defensins and β-defensins, C-type lectins, cathelicidin, lysozyme and intestinal alkaline phosphatase) support and mediate the biochemical barrier 29. Secretory immunoglobulin A and lymphoid follicles that contain a variety of immune cells, including B cells, T cells, dendritic cells and neutrophils, are the components of immune system barrier 28. Gut barrier dysfunction results in translocation of microbes, their secreted metabolites and other microbial products from the gut lumen into blood and lymphatics, allowing them to reach other tissues and organs including the liver 30 31…”
Section: Gut Barrier Dysfunction In Patients With Nafldmentioning
confidence: 99%
“…The combination of poly(I:C) and R848 with FVIII in absence of LPS resulted in less DC activation ( Figure S1B). 21 We show here that under in vitro conditions a combination of 1000 pg/mL LPS plus a second danger signal and FVIII is sufficient to induce a strong DC and subsequent T cell activation. 20 These plasma endotoxin levels can increase in different clinical setting for example upon (sub-) clinical infections or in patients with a leaky-gut syndrome.…”
Section: Discussionmentioning
confidence: 68%